Micronucleus formation assay and phagocytic index in mice administered water leaf extracts of Camellia sinensis - Salih, Shahlaa M.; Ebraheem, Rukaya M.; Saleh, Bushra H. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Green tea Camellia sinensis is non fermented tea. The tea is an infusion of flavorful leaves that has been consumed for centuries as a beverage and is valued for its medicinal properties. Over the last few decades green tea has been subjected to many scientific and medical studies to determine the extent of its long-purported health benefits, with some evidence suggesting regular green tea drinkers may have lower chances of heart disease and developing certain types of cancer. Green tea has also been claimed useful for weight loss management.Methods: Three doses of the hot water extract were used (19.2, 38.4 and 57.6 mg/kg) to investigate micronucleus formation and phagocytic index. Mice were divided into two groups. Group one; control and group two; mice were administered with three doses of the green tea extract orally as a single dose (0.1 ml) per day for 7 days. Then the mice were sacrificed in day 8 for immunological and cytogenetic assessments.Results: Results revealed that the first and third doses of green tea hot water extract were significantly effective in enhancing the values of phagocytic index and reducing micronucleusformation.Conclusions: Hot water may be a good solvent to extract active component from Camellia sinensis especially catechin, polyphenols, polysaccharides, flavonoids and vitamins. The high dose of hot water extracts of Camellia sinensis showed an excellent enhancing effects on the function of immune system of mice, moreover, reduction in micronucleus formation was recorded at such dose.